Human placental mesenchymal stem cells ameliorate chemotherapy-induced damage in the testis by reducing apoptosis/oxidative stress and promoting autophagy - Jiafeng Lu; Zhenxing Liu; Mingkai Shu; Liya Zhang; Wenjuan Xia; Liuna Tang; Jincheng Li; Boxian Huang; Hong Li (Stem Cell Research & Therapy, 2021)
Abstract Background The side effects of busulfan on male reproduction are serious, so fertility preservation in children undergoing busulfan treatment is a major worldwide concern. Human placental mesenchymal stem cells (hPMSCs) have advantages such as stable proliferation and lower immunogenicity that make them an ideal material for stimulating tissue repair, especially restoring spermatogenesis. The protective effects of hPMSCs in busulfan-induced Sertoli cells and in busulfan-treated mouse testes have not been determined. Our study aimed to elaborate the protective effect and potential mechanisms of hPMSCs in busulfan-treated testes and Sertoli cells. Methods First, we developed a mouse model of busulfan-induced testicular toxicity in vivo and a mouse Sertoli cell line treated with busulfan in vitro to assess the protective effect and mechanisms of hPMSC treatment on spermatogenesis. Then, the length, width, and weight of the testes were monitored using Vernier calipers. Furthermore, at 1 week and 4 weeks after the transplantation of hPMSCs, histological sections of testes were stained with hematoxylin-eosin, and the seminiferous tubules with fluid-filled cavities were counted. Through ELISA analysis, testosterone levels and MDA, SOD, LDH, and CAT activities, which are associated with ROS, were detected. Markers of ROS, proliferation (Ki67), and apoptosis (Annexin V) were evaluated by FACS. Next, the fluorescence intensity of proliferation markers (BrdU and SCP3), an antioxidant marker (SIRT1), a spermatogenesis marker (PLZF), and autophagy-related genes (P62 and LC3AB) were detected by fluorescence microscopy. The mRNA expression of γ-H2AX, BRCA1, PARP1, PCNA, Ki67, P62, and LC3 was determined by qRT-PCR. Results hPMSCs restored disrupted spermatogenesis, promoted improved semen parameters, and increased testosterone levels, testis size, and autophagy in the testis toxicity mouse model induced by busulfan. hPMSCs suppressed the apoptosis of Sertoli cells and enhanced their rate of proliferation in vitro. Additionally, hPMSCs protected against oxidative stress and decreased oxidative damage in the testis toxicity mouse model induced by busulfan. Furthermore, hPMSCs increased the expression of proliferation genes (PCNA and KI67) and decreased the mRNA levels of apoptotic genes such as γ-H2AX, BRCA1, and PARP1. Conclusions This research showed that hPMSC injection ameliorated busulfan-induced damage in the testis by reducing apoptosis/oxidative stress and promoting autophagy. The present study offers an idea for a new method for clinical treatment of chemotherapy-induced spermatogenesis.